Household optimising tax behaviours - Krasucka, Maja (Optymalizacyjne zachowania podatkowe gospodarstw domowych, 2011)
The article presents the issue of the tax behaviours of households oriented towards the optimisation of tax burden. The author shows how tax attitudes and behaviours are influenced by such factors as the strictness of the tax system and willingness to co-operate. Besides this, she presents the problem of tax planning. Using personal income tax as an example, the article presents available solutions allowing active taxpayers to pursue a strategy oriented towards the optimisation or reduction of the amount of paid taxes. The conducted analysis seems to indicate that the execution of a long-term tax burden optimisation strategy is possible practically in a limited scope and available to those households which achieve capital income, income from property rental or those undertaking to conduct business activities
Nauki i Finansach = Financial Sciences, 2011, Nr 1 (6), s. 193-207
Keywords: household; personal income tax; tax strategy; tax reliefs